Vulgar acts of entrenchment:The depiction of the Zimbabwean postcolony in Chenjerai Hove's 'Palaver finish' - Javangwe, Tasiyana D. (Unisa Press, 2016)
This paper seeks to interpret Chenjerai Hove's depiction in Palaver Finish of the Zimbabwean postcolony in the period leading into the new millennium. It seeks to argue that the portrayal of political developments in Zimbabwe in that period presents the nation as plunging into a state of vulgarity where human life and dignity are sacrificed at the expense of political power. Vulgarisation in this sense refers to gross distortions by the ruling party and state authority and the machinery of discursive processes, morality, culture and social life — all in an attempt to retain power. It also refers to the manner of doing things, to the use of the obscene, whether this is through the ab/use of language in its literal or metaphorical sense, dehumanizing sex or violence or disregard of civic etiquette.